Penerapan Sistem Hr Analytics di Berbagai Perusahaan Indonesia yang Bergerak di Industri Manufaktur - Alden Nelson; Mualifah Nurhidayati; Sheril Fitri Riana; Mischelle Lo; Jovina Jovina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The manufacturing industry is an industry that utilizes human resources on a large scale, so an HR system is needed that can properly manage its human resources. HR systems in manufacturing are usually used to manage shifts, overtime data, management of attendance. The purpose of this study is to determine the existing HR analytic implementation system in the manufacturing industry in Indonesia. The research method used is to use qualitative research which will provide output in the form of data that describes Tools for HR analytics as a topic or issue to be discussed. The source of data collection used is in the form of secondary data where this data is obtained through data that has been analyzed by previous studies with the intention of collecting various processed data. The results of this study indicate that large companies in Indonesia engaged in the manufacturing sector have implemented software from HR analytics that can be used by the HR division to facilitate the entire system related to HR in each company. It can be said that the HR analytics system is very useful and useful for companies in carrying out overall management related to human resources.